A Solvent‐Based Strategy for Tuning the Internal Structure of Metallo‐Folded Single‐Chain Nanoparticles. Issue 13 (11th May 2016) - Basasoro, Senda; Gonzalez‐Burgos, Marina; Moreno, Angel J.; Verso, Federica Lo; Arbe, Arantxa; Colmenero, Juan; Pomposo, José A.
Abstract : Controlling the spatial distribution of catalytic sites in metallo‐folded single‐chain nanoparticles (SCNPs) is a first step toward the rational design of improved catalytic soft nano‐objects. Here an unexplored pathway is reported for tuning the internal structure of metallo‐folded SCNPs. Unlike the conventional SCNP synthesis in good solvent (protocol I), the proposed new route (protocol II) is based on the use of amphiphilic random copolymers and transfer, after SCNP formation, from selective to good (nonselective) solvent conditions. The size and morphology of the SCNPs obtained by the two protocols, and the corresponding spatial distribution of the catalytic sites, have been determined by combining results from size exclusion chromatography with triple detection, small‐angle X‐ray scattering and molecular dynamics (MD) simulations. Remarkably, the use of these protocols allows the tuning of the internal structure of the metallo‐folded SCNPs, as supported by MD simulations results. While the conventional protocol I yields a homogeneous distribution of the catalytic sites in the SCNP, these are arranged into clusters in the case of protocol II. Abstract : An unexplored pathway is described for tuning the internal structure of metallo‐folded single‐chain nanoparticles, based on the use of amphiphilic random copolymers and two different synthesis protocols.